2004
DOI: 10.1542/peds.2004-0759
|View full text |Cite
|
Sign up to set email alerts
|

“Social Medication” and the Control of Children: A Qualitative Study of Over-the-Counter Medication Among Australian Children

Abstract: ABSTRACT. Objective. The aim of the study was to identify the patterns of use of over-the-counter (OTC) medications among children.Methods. The study used a qualitative design, with in-depth interviews of 40 parents with children <5 years of age.Results. There were 3 striking and readily apparent themes in the use of OTC medications among children. One was the administration of OTC medications as a form of "social medication," to give parents control over children's behavior that they perceived as fractious an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 31 publications
6
66
0
9
Order By: Relevance
“…Within trajectories of codeine misuse and dependence, a wide ranging profile of codeine user exists; for example, the elderly (Roumie & Griffin, 2004;Agaba et al 2004); youth (Elwood, 2001;Peters et al 2003Peters et al , 2007aPeters et al , 2007bPeters et al , 2007cFord, 2009;Lao et al 2010;Wilson et al 2010;Tang et al 2012;Agnich et al 2013); parents (Allotey et al 2004); students (Acocella, 2005); pharmacy customers (Sweileh et al 2004;Albsoul-Younes et al 2010); drug and psychiatric treatment patients (Agyapong et al 2013); addiction treatment patients (Akram & Roberts, 2003;Myers et al 2003;Yang & Yuan, 2008;Cohen et al 2009;Thekiso & Farren, 2010;Cooper, 2013b) and internet drug forum users (Van Hout, 2015) each with their own motives, patterns and outcomes for use. However, there is a lack of consensus around a definition of misuse of pharmaceutical opioid narcotics (Barrett et al 2008;Casati et al 2012;Cooper, 2013a) with broad misuse of pharmaceutical definitions including incorrect but legitimate use for medical purposes; use outside of acceptable medical guidelines when self-medicating at higher doses and for longer than advised; use for reasons other than for the instructions on the label or the intended purpose; recreational use for intoxication purposes; and where risks and adverse consequences outweigh the benefits (Nielsen et al 2008;Casati et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Within trajectories of codeine misuse and dependence, a wide ranging profile of codeine user exists; for example, the elderly (Roumie & Griffin, 2004;Agaba et al 2004); youth (Elwood, 2001;Peters et al 2003Peters et al , 2007aPeters et al , 2007bPeters et al , 2007cFord, 2009;Lao et al 2010;Wilson et al 2010;Tang et al 2012;Agnich et al 2013); parents (Allotey et al 2004); students (Acocella, 2005); pharmacy customers (Sweileh et al 2004;Albsoul-Younes et al 2010); drug and psychiatric treatment patients (Agyapong et al 2013); addiction treatment patients (Akram & Roberts, 2003;Myers et al 2003;Yang & Yuan, 2008;Cohen et al 2009;Thekiso & Farren, 2010;Cooper, 2013b) and internet drug forum users (Van Hout, 2015) each with their own motives, patterns and outcomes for use. However, there is a lack of consensus around a definition of misuse of pharmaceutical opioid narcotics (Barrett et al 2008;Casati et al 2012;Cooper, 2013a) with broad misuse of pharmaceutical definitions including incorrect but legitimate use for medical purposes; use outside of acceptable medical guidelines when self-medicating at higher doses and for longer than advised; use for reasons other than for the instructions on the label or the intended purpose; recreational use for intoxication purposes; and where risks and adverse consequences outweigh the benefits (Nielsen et al 2008;Casati et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of evidence for the effectiveness of many over-the-counter (OTC) medications [24,25], and the possible risks associated with their improper use among young children, [26,27], they remain widely used [28].The results of our study showed high prevalence of parental self-medication use among children 62.9%. These results are consistent with another study in Saudi Arabia reported that 53.8% of the parents practiced self-medication in their children [29].This proportions consistent with the global variation of prevalence of self-medication which has been reported by various studies to range between 30-70% [30].…”
Section: Discussion:-mentioning
confidence: 63%
“…It is expected that the use of OTC medications for symptom management in children will further increase [39]. Since in the present study, ChamBell-5-02 was shown to be safe, excellently tolerated and to reduce symptoms of teething, ChamBell-5-02 could be advised in the support of self-management of teething in children.…”
Section: Discussionmentioning
confidence: 69%